Childish urbanism: a cartographic experience that claims the aesthetic dimension of cities (PerCursos, 2021)
contributions to the apprehension of aesthetic aspects of the urban landscape will be reported, which enabled the approximation with a childish landscape perspective. The urbanism seen from its contradictions and at the height of the eyes of the children, allows to experience gestural articulations and theoretical managements that face the hegemonic convictions present in the discussions of the cities. With sensitive cartography as a methodological approach, three different devices were practiced with groups of children during walks in the public space. In order to bring contemporary treatment to the observations of these paths, the contributions of childhood as agents of urban life offer support for urgent reflection through aesthetic propositions of the city.
Keywords: Urban childhoods; Sensitive cartography; Contemporary urbanism